2021
DOI: 10.1002/app.50677
|View full text |Cite
|
Sign up to set email alerts
|

Construction of thermoplastic cellulose esters matrix composites with enhanced flame retardancy and mechanical properties by embedding hydrophobic magnesium hydroxide

Abstract: Biomass‐based composites with renewability and biodegradability have attracted extensive researches, but their applications are hindered by poor mechanical properties and flame retardancy. Cellulose ester matrix composites (CEMC), a kind of biomass‐based composites, were prepared with inorganic crystals as flame retardant and reinforcement. Cellulose acetate oleate (CAO) prepared by mechanical activation‐assisted solid‐phase reaction was used as thermoplastic matrix. Hydrophobic oleate‐magnesium hydroxide (O‐M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…5,13,19 Noh et al used hexylphosphoric acid (HPA) to modify the surface of MH nanoparticles to obtain a hydrophobic surface and make MH more uniformly dispersed at a MH content of 50 wt%. 20 Zhang et al found that MH modified with hydrophobic oleic acid could be better dispersed in the cellulose acetate oleate (CAO) matrix compared to unmodified MH and the tensile strength and LOI value were increased by 16.6% and 41.9%, respectively, 21 which was attributed to the improved dispersion of O-MH and the close combination of O-MH and CAO. Liu et al prepared oil-extended styrene-ethylene-butadiene-styrene (O-SEBS)polypropylene (PP) using MH modified with triethoxysilane and polymethyl-vinyl silicone rubber.…”
Section: Introductionmentioning
confidence: 99%
“…5,13,19 Noh et al used hexylphosphoric acid (HPA) to modify the surface of MH nanoparticles to obtain a hydrophobic surface and make MH more uniformly dispersed at a MH content of 50 wt%. 20 Zhang et al found that MH modified with hydrophobic oleic acid could be better dispersed in the cellulose acetate oleate (CAO) matrix compared to unmodified MH and the tensile strength and LOI value were increased by 16.6% and 41.9%, respectively, 21 which was attributed to the improved dispersion of O-MH and the close combination of O-MH and CAO. Liu et al prepared oil-extended styrene-ethylene-butadiene-styrene (O-SEBS)polypropylene (PP) using MH modified with triethoxysilane and polymethyl-vinyl silicone rubber.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] Despite its attractive properties, MH is a hydrophilic material with high interfacial energy and poor compatibility with hydrophobic polymers. [22][23][24] MH particles are highly aggregated in polymer matrix and are difficult to form homogeneous and stable composites. 25 In addition, 60 wt% MH is usually required to ensure the desired flame retardancy of the material, which leads to a dramatic reduction in the processability and toughness of the polymer.…”
Section: Introductionmentioning
confidence: 99%
“…Magnesium hydroxide (MH) is an environmental, friendly nonhalogenated flame retardant filler, which has been widely studied for its low smoke, nontoxic, noncarcinogenic gas, and other advantages 19–21 . Despite its attractive properties, MH is a hydrophilic material with high interfacial energy and poor compatibility with hydrophobic polymers 22–24 . MH particles are highly aggregated in polymer matrix and are difficult to form homogeneous and stable composites 25 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, OA reacted with brucite, magnesium oleate was formed on the surface of brucite. The presence of magnesium oleate can reduce the surface polarity of brucite and promote the homogeneous dispersion of brucite in the LDPE matrix, which also can improve the flame retardancy of LDPE composite 44,45. 4.7 | Mechanical properties of LDPE/ brucite composites…”
mentioning
confidence: 99%